Impacts of climatic condition and its change on the temperature suitability and potential productivity of rice in the Yangtze River delta of China - LI Quan-sheng; YE Xu-jun; YANG Zhong-en (浙江大学学报. 农业与生命科学版)
This paper presents the temperature suitability assessment function and the calculation models of potential productivity for crops, and determined the relevant parameters for rice according to field tests and statistic analysis, and analyzed the impacts of climatic condition and its change on the suitability of temperature for rice at different developmental stages and the rice potential productivity in the Yangtze River delta of China. Results indicated the climatic change had ameliorated the temperature condition at the transplanting and tillering stage and the grain filling and maturing stage of the first crop rice, and the heading and flowering stage and the grain filling and maturing stage of the second crop rice. In terms of the average value of the temperature suitability assessment of the above 4 stages, the average of the duration from 1981 to 1997 was higher than that of the duration from 1951 to 1980, being 11.1%, 5.2%, 13.4% and 13.2% up respectively. From the point of view of the potential productivity, the light potential productivity of the first crop rice, the light and the light-temperature potential productivity of the second crop rice all showed a trend of decreasing except the light-temperature potential productivity of the first crop rice, which showed a significant increase. However, since the 1980s the decreasing trend of potential productivity has reduced.